Complex Internal Microstructure of Feather Follicles on Chicken Skin Promotes the Bacterial Cross-Contamination of Carcasses During the Slaughtering Process - Zhang, Xibin; Peng, Zixin; Li, Peng; Mao, Yanwei; Shen, Ru; Tao, Rui; Diao, Xiuguo; Liu, Longhai; Zhao, Yuzhong; Luo, Xin (Frontiers in Microbiology, 2020)
Chicken skin is considered the most susceptible to bacterial contamination during slaughter. It is rich in bushy feather follicles with complex internal structures that can absorb bacteria via cross-contamination during slaughter. Until now, the microstructural changes and local bacterial composition of feather follicles during slaughter have not been thoroughly investigated. This study used Hematoxylin-Eosin (HE) staining of the tissue paraffin section to investigate the structure of the feather follicles on chicken skin. Furthermore, the biopsy sampling method was employed for the high-throughput sequencing of 16S RNA genes to study the composition and source of bacterial contamination during slaughter. The results showed that the feather follicles on the chicken skin formed a closed cavity structure during the slaughtering process. The volume of the irregular follicle cavity was about Ø: 200μm × D: 1040 μm, which provided a place for the bacteria to absorb and resist the cleaning and disinfection during the slaughtering process. The composition of bacteria in the feather follicle was mainly Acinetobacter (37%), Psychrobacter (8%), Macrococcus (5%), and Comamonas (2%). The heat map obtained via the species abundance analysis of the feather follicle samples, as well as the slaughter environment samples, suggested that the gastrointestinal feces contaminated the feather follicles on the chicken skin mainly during the evisceration, defeathering, and pre-chilling processes, and the last stage chilling water also caused severe cross-contamination to in the feather follicles during the pre-chilling process.